2015
DOI: 10.3389/fpls.2015.00300
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and expression analysis of the NPR1-like gene family from Persea americana (Mill.)

Abstract: The NONEXPRESSOR OF PATHOGENESIS-RELATED GENES1 (NPR1) forms an integral part of the salicylic acid (SA) pathway in plants and is involved in cross-talk between the SA and jasmonic acid/ethylene (JA/ET) pathways. Therefore, NPR1 is essential to the effective response of plants to pathogens. Avocado (Persea americana) is a commercially important crop worldwide. Significant losses in production result from Phytophthora root rot, caused by the hemibiotroph, Phytophthora cinnamomi. This oomycete infects the feeder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 80 publications
9
48
2
1
Order By: Relevance
“…Sin embargo, los resultados siguieren que los cambios de expresión de PR-5 en tejidos infectados por ASBVd no fueron inducidos por PaNPR1, debido a que los niveles de expresión de éste no muestran diferencias significativas con respecto a la expresión basal. Backer et al (2015) reportaron que la expresión constitutiva basal de PaNPR1 fue más alta en hojas que en frutos inmaduros; además, y a diferencia del conocimiento que se tiene donde el ácido salicílico es activador de NPR1, los autores encontraron una regulación negativa de PaNPR1 en el tratamiento con ácido salicílico a las 12h después de la aplicación, lo que sugiere una función alternativa en las respuestas de defensa.…”
Section: Palabras Clave: Avocado Sunblotch Viroid Persea Americana unclassified
See 2 more Smart Citations
“…Sin embargo, los resultados siguieren que los cambios de expresión de PR-5 en tejidos infectados por ASBVd no fueron inducidos por PaNPR1, debido a que los niveles de expresión de éste no muestran diferencias significativas con respecto a la expresión basal. Backer et al (2015) reportaron que la expresión constitutiva basal de PaNPR1 fue más alta en hojas que en frutos inmaduros; además, y a diferencia del conocimiento que se tiene donde el ácido salicílico es activador de NPR1, los autores encontraron una regulación negativa de PaNPR1 en el tratamiento con ácido salicílico a las 12h después de la aplicación, lo que sugiere una función alternativa en las respuestas de defensa.…”
Section: Palabras Clave: Avocado Sunblotch Viroid Persea Americana unclassified
“…However, results in this research suggest that changes in PR-5 expression on tissue infected by ASBVd were not produced by changes in PaNPR1 expression because it did not change significantly from basal. Backer et al (2015) reported that PaNPR1 constitutive expression was higher on leaves than on unripe fruits. Additionally, and contrary to documented reports on NPR1 activation by salicylic acid, they found PaNPR1 down-regulation 12 h after salicylic acid treatment; this behavior suggests an alternative function for defense responses.…”
Section: Palabras Clave: Avocado Sunblotch Viroid Persea Americana mentioning
confidence: 99%
See 1 more Smart Citation
“…observed that resistance of avocado roots to P. cinnamomi infection was associated with more rapid β-1,3-glucanase and superoxide dismutase activities as soon as 6 hpi in a resistant variety. By measuring expression levels of five defence-related NPR1-like genes after treatment with salicylic acid (SA), jasmonic acid (JA) and inoculation with P. cinnamomi, Backer et al (2015) found that at 12 hpi, expression of PaNPR2 and PaNPR4 was significantly lower in the resistant variety 'Dusa' than in the susceptible variety 'R0.12'. It is suggested that the switch from biotrophic to necrotrophic growth may occur around this time, and that in 'R0.12', increased expression of PaNPR1-like defence-related genes may suppress the JA/ET pathway, relative to 'Dusa', which perceives and reacts to the change in growth habit more quickly.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects of resistance include the following: (I) root regenerative ability , (II) attractiveness to zoospores in terms of either encystment rates (Aveling & Rijkenberg, 1991 or the concentration and composition of exudates produced by the roots , Zilberstein & Pinkas, 1987, (III) deposition of structural barriers such as callose and tyloses , Dugger & Zentmyer, 1981, (IV) the induction of various biochemical defence pathways within avocado roots in response to P. cinnamomi infection , García-Pineda et al, 2010, Romero-Correa et al, 2014, Backer et al, 2015. The approaches outlined above involve identification of a resistant phenotype before association with the corresponding genotype.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%